Evaluation of anthocyanin extracted from Lempeni (Ardisia Elliptica l.) fruit as a new natural acid-base indicator - Rahma, U.; Zulfajri, M.; Ismulyati, S. (International Journal of Biology and Chemistry, 2025)
The Ardisia elliptica species is usually known as Lempeni fruit has a purplish red color which contains the color pigment of anthocyanins. This work aimed to obtain anthocyanins from Lempeni fruit and applied them as new acid-based indicators. The extraction method was carried out using a combination solvent containing ethanol and HCl with appropriate ratio, followed by the addition of anthocyanin-containing extract with acid and base solutions. The results showed that anthocyanin from Lempeni fruit induced a signicant color response depending on the pH values of acid-base solutions. The color was changed to red in acidic environments and brownish green in alkaline environments. Besides, the filter paper indicator and acid-base titrations were performed with good performances. The utilization of a natural acid-base indicators from anthocyanins offers potential applications in qualitative analysis and scientific education, by exploring new sources of anthocyanins. This research contributes to the understanding of the potential use of anthocyanins from Lempeni fruit in environmentally friendly and economical analytical chemistry applications. Keywords: Extraction, Anthocyanin; Lempeni fruit; Natural indicator; Acid base.